1981
DOI: 10.1103/physrevlett.47.95
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic-Wave Excitation in a Large Laboratory Beam-Plasma System

Abstract: Electromagnetic radiation is observed when an electron beam is injected into a uniform quiescent magnetoplasma. The emission peaks near the electron plasma frequency (oo ^(X> P »UJ C ) and is found to result from the scattering of unstable intense electrostatic plasma waves off self-consistently produced ion acoustic waves with wave vectors k^ k e . The emission is localized, polarized, and negligible in intensity at w = 2oo pe . Space-time growth and co-k properties of the three-wave interaction are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Related processes in laboratory plasmas have also been discussed by, e.g. Hutchinson et al (1978), Benford et al (1980), Whelan & Stenzel (1981), Intrator et al (1984), Whelan & Stenzel (1985). Furthermore, radio bursts of millisecond duration were recently discovered in the 1 GHz band Loeb et al (2014), with strong evidence that they come from ∼1 Gpc distances, implying extraordinarily high-brightness temperature.…”
Section: Introductionmentioning
confidence: 98%
“…Related processes in laboratory plasmas have also been discussed by, e.g. Hutchinson et al (1978), Benford et al (1980), Whelan & Stenzel (1981), Intrator et al (1984), Whelan & Stenzel (1985). Furthermore, radio bursts of millisecond duration were recently discovered in the 1 GHz band Loeb et al (2014), with strong evidence that they come from ∼1 Gpc distances, implying extraordinarily high-brightness temperature.…”
Section: Introductionmentioning
confidence: 98%
“…16,17 In the context of electron beam-plasma experiments, radio emission has been observed, and different interpretations involving mode conversion, and/or strong/weak turbulence have been advanced. [18][19][20][21] For most type III bursts, analytical work has shown that plasma emission is the dominant mechanism. 22,23 Plasma emission is also responsible for other solar and interplanetary radio emissions; e.g., type II solar radio bursts and 2 -3 kHz radio emission in the outer heliosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Classic examples are the solar type II and III radio bursts (Goldman 1983;Melrose 1985;Robinson & Cairns 1998a, 1998b, 1998c. Laboratory beam-plasma interaction experiments also demonstrate plasma emission or equivalent phenomenon (Hutchinson et al 1978;Benford et al 1980;Whelan & Stenzel 1985a, 1985bIntrator et al 1984). One of the most commonly accepted mechanisms for the 2H EM emission involves the merging of two oppositely traveling Langmuir waves, compactly expressed as L+L → 2H, where L stands for the primary Langmuir wave traveling along the electron beam, while L represents the backscattered Langmuir wave traveling opposite to L. Here, 2H stands for the 2H EM wave.…”
Section: Introductionmentioning
confidence: 99%